Praktik Hegemoni Mahasiswa Senior Terhadap Junior Di Dalam Kehidupan Kampus: Hegemonic Practices of Upperclassmen to Freshmen Within College Life - Muhammad Syukur (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
The research aims to explain: 1) Forms of hegemonic practices of upperclassmen to freshmen in college life at the State University of Makassar and 2) Levels of hegemonic practices of upperclassmen to freshmen at the State University of Makassar. This research is qualitative descriptive with snowball sampling technique used to determine the participants which consist of 25 upperclassmen and 20 freshmen class of 2018 and 2019 academic year. Data collection methods included observation, interview and documentation. Data analysis technique consists of three stages, namely: data reduction, data presentation and conclusion drawing. Data verification was conducted through observation perseverance and source and time triangulation. The results show that 1) forms of hegemonic practices of the upperclassmen to freshmen at the State University of Makassar include agreement, domination and intellectual leadership and moral and 2) the level of hegemony conducted by the upperclassmen at the State University of Makassar is in the decadent hegemony level. Relationship between upperclassmen and freshmen is good but only few freshmen who established intimacy. There is awkwardness between the upperclassmen and the freshmen during interaction. Freshmen are active in supporting the upperclassmen in student clubs at the department, faculty as well as university levels. It is because the freshmen feel reluctant if they do not carry out the upperclassmen direction. In addition there is also a sense of compulsion due to sanction used by the upperclassmen.